CHALLENGES IN ONLINE ASSESSMENT: THE CASE OF INDONESIAN TEACHERS - Diah Kurniati; Ahdi Riyono; Budi Utomo (Bajang Institute, 2023)
Since face-to-face classrooms are shifted to online classes, the assessment which is a part of the teaching-learning process is also virtually conducted. This study aims to describe the online assessment tools utilized by teachers when giving online assessments to their students. Moreover, it also investigates the challenges faced by teachers in the implementation of online assessment as well as the solution to respond to those issues. This is a qualitative research design using open-ended questionnaires as the instrument of the research. The participants were 25 teachers from primary schools, junior high schools, and senior high schools in Central Java province Indonesia. The findings of the research show that teachers from elementary schools to senior high schools use a range of online assessment tools when giving their students online evaluations such as Google Forms, WhatsApp, Quippier, Quizzes, and Microsoft Team. When giving online assessments, several difficulties are encountered by teachers at all levels, including poor internet access, academic dishonesty, students’ discipline, and the lack of mobile phones. Teachers have done various actions in response to such problems. For instance, changing the questions from objective to subjective ones, providing internet access, encouraging students to submit their work on time, and visiting the students at home to lend them mobile phones to do assessments if they do not have one.